FINANCIAL BEHAVIOR: FINANCIAL LITERACY, FINANCIAL INCLUSION, LIFESTYLE, AND LOCUS OF CONTROL - Raindra, Nadya Nur; Paramitalaksmi, Ratri (JURNAL MUTIARA AKUNTANSI, 2024)
Not only the younger generation out there, at Universitas Mercu Buana Yogyakarta alone, many students access financial services, especially QRIS as one of the non-cash payment methods. This level of ease in accessing financial services allows students to fulfill their lifestyle. This study aims to determine whether financial literacy, lifestyle, and financial inclusion of undergraduate accounting students at Mercu Buana University Yogyakarta also have a significant effect on the personal financial behavior of each student. This study uses the strata method in quantitative research through distributing questionnaires. The population of this study were students of Universitas Mercu Buana Yogyakarta, class of 2021-2023. The sample chosen to be the sample in this study is the Gen Z group which is financially and each generation has different financial habits. This study shows the first result, that financial literacy does not affect financial behavior, financial inclusion affects financial behavior, lifestyle does not affect financial behavior, and locus of control affects financial behavior. However, together, financial literacy, financial inclusion, lifestyle, and locus of control affect financial behavior. for generation Z, in this current era, they must understand more about finance and deepen financial literacy. This financial literacy can help Generation Z to understand more about finance. The wise use of financial inclusion can also affect the financial behavior of each person. The current lifestyle of generation Z greatly affects financial behavior. Financial behavior in each generation Z person can be controlled by self-awareness carried out by oneself.